Informal settlement upgrading in the current policy context: lessons from the Civic Movement in Lebowakgomo in Limpopo Province, 1990-2000 - Sepuru, David Mmakgabo Champ (My University, 2010)
The national and provincial departments of housing and local authorities can draw incredible lessons from the integrated approach of the Civic Movement in Lebowakgomo which is similar in many respects with major tenets of Chapter 13 of the National Housing Code in their endeavours to upgrade informal settlements in this country. The approach employed in this study hinges on a desktop study of grey and secondary literature, audio material in the form of information dissemination cassette complimented by the living memory of the only two respondents that I interviewed as well as my personal experience derived from my tenure as the Chairperson of the local branch of SANCO, Councillor for Ward 3, Chairperson (all Mayors of rural Transitional Local Councils (TLCs) were referred to as Chairpersons) of Greater Lebowakgomo TLC and the TLC Rep in the Northern District Council (NDC). These methods and procedures revealed that the Civic Movement approach encompassed major tenets of Chapter 13 of the National Housing Code, centred on concepts of urban-rural linkages, secure tenure, community participation and eradication of informal settlements and the peoplecentred and people-driven processes.